Sumbangan Taman Pendidikan Al Qur'an Terhadap Peningkatan Ibadah Bagi Anak Di Madrasah Ibtidaiyah Muhammadiyah Giriroto Tahun 2014/2015 - Rahmad, Nur; , Drs. Bambang Raharjo, M.Ag; , Drs. Arief Wibowo, M.Ag (2015)
Taman Pendidikan Al-Qur'an (TPA) is an agency outside the school education (non-formal), which has a kind of religious teaching load more emphasis on the religious aspect with reference to its main sources, namely the Qur'an and Sunnah. The study goal was to determine the contribution of education park Qur'an to the improvement of worship for children in Muhammadiyah Islamic elementary schools Giriroto year 2014/2015. The research approach used in this study is a qualitative method. Researchers using interviews, documentation, and observation as a tool to collect data. Data analysis in this peneliian authors using the inductive method. inductive method is a way of thinking that starts with the reasoning that have characteristics and limited in scope and then drawn a conclusion of a general nature. Donations Wildlife Education Koran against Muhammadiyah Islamic Elementary Giriroto namely (1) the material is more predominant religious teaching in the TPA makes the students more quickly in terms of the ability to worship. (2) teaching methods TPA which provides direct attention on each student (people), making students more clearly and understand in learning, especially in the practice of worship. and (3) more time to make the learning process more focused on landfill.